1985
DOI: 10.1530/jrf.0.0750653
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and parturition in rats after sympathetic denervation of the ovary, oviduct and utero-tubal junction

Abstract: The ovarian vascular pedicle and ovarian suspensory ligament were briefly frozen to destroy the nerves. Examination of sections from the ovary, oviduct and utero-tubal junction by fluorescence histochemistry showed that they were usually devoid of adrenergic nerves. Measurement of noradrenaline in segments of the uterine horn by high-performance liquid chromatography showed that the transmitter was eliminated from the upper third but not the middle or lower thirds of the uterine horn. Unilateral or bilateral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…A neurectomyinduced delay in the fall in systemic progesterone contrasts with reports that earlier in pregnancy, transection of the pelvic nerve, as well as the vagus nerve, was associated with reduced serum progesterone [13,48], the significance of which is uncertain because preterm birth did not occur. Nonetheless, the finding that innervation of the cervix may influence ovarian function during pregnancy could reflect efferent control by a local and more central parasympathetic pathway [49,50]. After pelvic nerve transections, there is a loss of afferent connections to local interneurons in the thoracolumbar spinal cord [14], as well as to ascending sensory pathways in the dorsal columns and autonomic intermediolateral columns of the spinal cord that project to brainstem regions, i.e., solitary nucleus and dorsal motor nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…A neurectomyinduced delay in the fall in systemic progesterone contrasts with reports that earlier in pregnancy, transection of the pelvic nerve, as well as the vagus nerve, was associated with reduced serum progesterone [13,48], the significance of which is uncertain because preterm birth did not occur. Nonetheless, the finding that innervation of the cervix may influence ovarian function during pregnancy could reflect efferent control by a local and more central parasympathetic pathway [49,50]. After pelvic nerve transections, there is a loss of afferent connections to local interneurons in the thoracolumbar spinal cord [14], as well as to ascending sensory pathways in the dorsal columns and autonomic intermediolateral columns of the spinal cord that project to brainstem regions, i.e., solitary nucleus and dorsal motor nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…These authors (Burden & Lawrence 1977) also found that denervation on days 10, 14 and 18 of pregnancy caused a decrease in the activity of the 5-3 -hydroxysteroid dehydrogenase enzyme which synthesises progesterone. However, Roche et al (1985) who performed the denervation on day 15 observed that it did not affect the normal development of gestation. On the other hand, Massa & Bruce (1994) have reported that, on day 16 of pregnancy, the secretion of ovarian progesterone is not modified when noradrenaline is injected into the ovarian artery in spite of modifying the arterial pressure.…”
Section: Introductionmentioning
confidence: 97%
“…The influence of the sympathetic innervation on the contractile activity of uterine smooth muscle around the time of implantation has been studied in rats (Roche et al, 1985;Legrand et al, 1987;. Surgical destruction of the ovarian nerve had no effect on either blastocyst transport or spacing (Roche et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the sympathetic innervation on the contractile activity of uterine smooth muscle around the time of implantation has been studied in rats (Roche et al, 1985;Legrand et al, 1987;. Surgical destruction of the ovarian nerve had no effect on either blastocyst transport or spacing (Roche et al, 1985). Injection of the a-adrenoceptor antagonists, prazosin and phenoxybenzamine, depressed electromyographical activity in the uterus of rats (Legrand et al, 1989), disrupted transport and implantation, and even spacing of foetuses did not occur (Legrand et al, 1987).…”
Section: Introductionmentioning
confidence: 99%